Pengaruh Intellectual Capital, Strategi Bisnis dan CSR terhadap Kinerja Keuangan Perusahaan - Febby Putri Dewany; Rilla Gantino (Universitas Pamulang, 2022)
This study aims to analyze the influence of intellectual capital, business strategy and corporate social responsibility on the financial performance of companies in an empirical study of the coal and pharmaceutical sub-sectors listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The method used in this research is purposive sampling. The number of samples used in this study were 30 companies. The type of data is secondary data sourced from financial reports and annual reports. The data analysis method used is multiple linear regression analysis. The test results show that simultaneously Intellectual Capital, Business Strategy and Corporate Social Responsibility have a significant effect on the Company's Financial Performance. Partially Intellectual Capital has a significant and positive effect on the Company's Financial Performance in the coal sub-sector and the pharmaceutical company sub-sector. Business Strategy has a significant and positive effect on the company's financial performance in the company's sub-sector, while the business strategy has no effect on the company's financial performance in the company's pharmaceutical sub-sector. Corporate Social Responsibility has no significant effect on the company's financial performance in the pharmaceutical sub-sector companies and pharmaceutical sub-sector companies.